1961
DOI: 10.1002/jpln.19610920203
|View full text |Cite
|
Sign up to set email alerts
|

Die Eiweißqualität von Körnern verschiedener Getreidearten in Abhängigkeit von Stickstoffversorgung und Entwicklungszustand

Abstract: In früheren Arbeiten (1, 2) ist über den Einfluß einer variierten N‐Düngung, insbesondere einer späten zur Zeit der Blüte verabreichten N‐Gabe, auf die Eiweißzusammensetzung des Gerstenkorns berichtet worden. Es konnte festgestellt werden, daß mit steigendem N‐Gehalt des Kornes dessen verschiedene Eiweiße in unterschiedlichem Ausmaß vermehrt werden. Zur Übersicht ist in Abb. 1 die Lokalisation der verschiedenen Eiweiße des Gerstenkornes, wie sie durch Extraktion gewonnen werden können, schematisch dargestellt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
1

Year Published

1961
1961
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…The globulin fraction accounts for the majority of total seed protein (1,13,14). The alcohol-soluble prolamin fraction, which is the major seed storage protein in most cereals, is very low in oats (1,6,11,13,14).In To determine the solubility of oat globulin under various conditions, the defatted flour was extracted with 1 M NaCl, 0.05 M Tris (pH 8.5) at a ratio of 100 ml/g, using magnetic stirring at room temperature for 1 to 2 hr. The extract was centrifuged for 20 min at 23 C and 27,000g, and the supernatant was dialyzed against two changes of distilled H20 at 4 C, precipitating the globulin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The globulin fraction accounts for the majority of total seed protein (1,13,14). The alcohol-soluble prolamin fraction, which is the major seed storage protein in most cereals, is very low in oats (1,6,11,13,14).In To determine the solubility of oat globulin under various conditions, the defatted flour was extracted with 1 M NaCl, 0.05 M Tris (pH 8.5) at a ratio of 100 ml/g, using magnetic stirring at room temperature for 1 to 2 hr. The extract was centrifuged for 20 min at 23 C and 27,000g, and the supernatant was dialyzed against two changes of distilled H20 at 4 C, precipitating the globulin.…”
mentioning
confidence: 99%
“…The globulin fraction accounts for the majority of total seed protein (1,13,14). The alcohol-soluble prolamin fraction, which is the major seed storage protein in most cereals, is very low in oats (1,6,11,13,14).…”
mentioning
confidence: 99%
“…It seems that, in the case of the first gel (Figure 1), some other protein fraction undissolved in the Na-phosphate buffer stayed in the protein pattern. This third protein fraction, that causes differences in the first protein patterns, could be called, in accordance with German authors Michael et al (1961), Völker (1975) and Wieser et al (1980), glutelin fraction.…”
Section: Discussionmentioning
confidence: 53%
“…It was also confirmed that oat grain contains another significant protein fraction -glutelins as German authors referred (Michael et al 1961, Völker 1975, Wieser et al 1980. The question of the protein fraction used for admixture identification remains still open.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation